Sources of resistance to wheat blast and its underlying mechnisim identified, resistant gene(s) introgressed and resistant varieties released in Bangladesh, India and Nepal - CGIAR Research Program on Wheat (2020)
Wheat blast has spread across continents, now present in South America (Brazil, Paraguay, Argentina, Bolivia), Asia (Bangladesh) and Africa (Zambia). Researchers have identified sources of resistance and the underlying resistance mechanism; also introgressed new resistant gene(s) to develop durable resistant varieties. Resistant varieties have been released in Bangladesh, Nepal and India; seed multiplication and dissemination is in progress. The pathogen’s population is clonal in Bangladesh with sensitivity to fungicides, and studies in Zambia about this aspect have just started.